Biblioteka pedagogiczna wsparciem dla dziecka z niepełnosprawnością, jego rodziców i wychowawców (na przykładzie Biblioteki Pedagogicznej w Skawinie) = Pedagogical library support for children with disabilities, theirparents, and their educators - Ippoldt, Lidia (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The pedagogical library, according to the Regulations of the Ministry of National Education, should collect, process, store and make available, among others, literature in the field of pedagogy and related sciences and materials related to theissue of providing psychological and pedagogical assistance to children and young people as well as parents and teachers. It should also organize and support schools and facilities in the implementation of didactic, educational and caring tasks, and inspire and promote reading and media education. The Pedagogical Library in Skawina supports educational institutions, also assisting them in working with children with disabilities. It provides their parents and teachers with literature in the field of psychology and bibliotherapy, and conducts not only training sessions and meetings in this area but also classes in schools and kindergartens with elements of fairy-tales and bibliotherapy. It also publishes therapeutic fairy-tales helpful for shaping the emotional development of children. Thanks to its activities, the institution has been regarded as a municipal centre for bibliotherapy.
Keywords: biblioteki pedagogiczne; Biblioteka Pedagogiczna w Skawinie; placówki oświatowe (współpraca); dzieci z niepełnosprawnością; świadomość społeczna; biblioterapia; pedagogical libraries; Pedagogical Library in Skawina; educational institutions (cooperation); children with disabilities; social awareness; bibliotherapy